Regular Low-Intensity Exercise Prevents Cognitive Decline and a Depressive-Like State Induced by Physical Inactivity in Mice: A New Physical Inactivity Experiment Model - Kim, Jimmy; Park, Jonghyuk; Mikami, Toshio (Frontiers in Behavioral Neuroscience, 2022)
Regular exercise has already been established as a vital strategy for maintaining physical health via experimental results in humans and animals. On the other hand, regarding physical inactivity, namely lack of physical activity, numerous human studies have reported that physical inactivity is a primary factor that causes obesity, muscle atrophy, metabolic diseases, and deterioration in cognitive function and mental health. However, an established animal experimental method to examine the effect of physical inactivity on physiological, biochemical, and neuroscientific parameters has yet to be reported. Here, we made a new rearing cage, named a physical inactivity cage (PI cage), for investigating the effect of physical inactivity on cognitive function and depressive-like state and obtained the following experimental results by its use. (1) Physical activity of mice in the PI cage was decreased to approximately half of that in the standard cage. (2) Physical inactivity via rearing in PI cages caused a cognitive decline and onset of a depressive-like state without increasing body weight and plasma corticosterone. (3) Physical inactivity decreased neuronal cell proliferation, blood vessel density, and gene expressions of vascular endothelial growth factor and brain-derived neurotrophic factor in the hippocampus. (4) Regular low-intensity exercise prevented cognitive decline and onset of a depressive-like state caused by physical inactivity. These results showed that rearing in the PI cage would be an adequate and valuable experimental method for examining the effect of physical inactivity on cognitive function and depressive-like state.